Economic Diversification of Saudi Arabia - Kyselová, Vivienn; Jiránková, Martina, 1967-; Abdallah, Kareem Issam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
Historically reliant on oil exports, Saudi Arabia introduced a plan of strategies intending to shift the country from excessive dependency on oil revenues. With regard to the global environmental concerns and the possible resource depletion, a transfer to a more sustainable economy with diversified revenue incomes is inevitable. Focus has been given to the development of non-oil sectors. The aim of this bachelor’s thesis is to assess the development of Saudi Arabia’s tourism sector in line with the diversification goals outlined in Vision 2030. This thesis consists of three chapters. First, the theoretical background of economic diversification and the key concepts associated with excessive reliance on commodity revenues are introduced. Reforms and regional trends in the GCC Region are introduced. The second chapter focuses on Saudi Arabia, currently the largest exporter of crude petroleum, making efforts to diversify its economy beyond the commodity sectors. Special attention is given to the Public Investment Fund’s role in driving investments across new sectors. The last chapter is devoted to the tourism sector, identified as a key pillar of the diversification strategy of Saudi Arabia. The thesis assesses the transformation of the sector from religious tourism to a broader offering, supported by the development of large projects under the Red Sea Global. A quantitative analysis of tourist arrivals, tourist spending and preferences of the tourists follows.
Vedoucí práce: Martina Jiránková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses